PENERAPAN PENGENDALIAN HAMA TERPADU (PHT) TERHADAP WERENG BATANG COKLAT NILAPARVATA LUGENS (Stal) (Homoptera: Delphacidae) PADA TANAMAN PADI DI KABUPATEN SUMENEP - Ach. Syarif N. Fajrullah; Gatot Mudjiono; Toto Himawan (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2015)
Integrated Pest Management (IPM) on study planthopper Nilaparvata lugens (Stal) (Homoptera: Delphacidae) on rice field in Sumenep district, conducted to learn the effect the implementation of Integrated Pest Management (IPM) on the planthoppers population and enemies naturalto maintain the productivity of rice plants. The research was conducted in the village of Pragaan Laok, District Pragaan, Sumenep, East Java Province in October 2013 until March 2014. The method used was experimental method. Variables include the observation of the population of brown plant hopper rod, the rod brown planthoppers natural enemies, the intensity of the attack, the growth of the rice plant, productive tillers, panicle length, number of grains, and the real tile production (harvest time) and grain yield. In this study, the data were analyzed using t test to compare observations between IPM treatment with conventional treatment. The observation and discussion shows that 1) The population of brown plant hopper rod was not significantly different in the treatment of PHT compared to conventional treatment, 2) The population of natural enemies brown plant hopper rod for predatory spider Lycosa sp higher in IPM treatment than conventional treatments while Paederus fuscipes Staphylinidae beetle population is higher than conventional treatment IPM treatment, 3) The intensity of the attack on the treatment of IPM and conventional treatment is below the economic threshold, 4) The growth of rice plants was not significantly different in the treatment of IPM compared to conventional treatment, 5) The development of tillers and number of tillers were not significantly different in the treatment of IPM compared to conventional treatment, 6) Long panicles were not significantly different in the treatment of IPM compared to conventional treatment, while the large number of rice grains IPM treatment is lower than conventional treatment, 7) The results of tile is higher than conventional treatment IPM treatment but the real result (at harvest) higher than IPM treatment compared to conventional treatment , and 8) Grain yield results are not significantly different at IPM treatment be compared conventional treatments.